Legality of Dismissal of Constitutional Court Judges During Their Term Of Office By The House of People’s Representatives (DPR) - Regita Mei Hijri Z. Abbas; Hendra Karianga; Rumkel, Nam (Fakultas Hukum Universitas Mataram, 2025)
Study This aiming to identify legality dismissal of a Supreme Court Judge Constitution within the term of office by the DPR, as well reviewing and analyzing models and patterns recruitment appointment and dismissal of Court judges Constitution. This type of research is normative. Normative legal research is the process of discovering legal rules, legal principles, and legal doctrines to address the legal problems faced. By identifying, describing and analyzing the legality of the dismissal of Constitutional Court judges during their term of office by the DPR, where the dismissal of Constitutional Court judges has been regulated in the law, and every action and authority of state institutions must be based on the applicable rules or norms. The approaches used in this research are the statuta Approach, Conseptual Approach and Comparative Approach. The legal materials used consist of Primary Legal Materials in the form of Legislation, Decisions, and other relevant legal documents and Secondary Legal Materials consisting of Books, Theses, Dissertations, Journals and other documents. Legal materials are collected using Literature Study techniques which are then analyzed qualitatively to obtain conclusions in the form of solutions to the problems studied. The results of this study indicate that the legality of the dismissal of Constitutional Court Judges during their term by the House of Representatives (DPR) is unconstitutional because there is no norm or authority granted to the DPR to dismiss Constitutional Court Judges it proposes. Future redesign of the appointment of constitutional judges is necessary to ensure that the loopholes for political intervention to erode the independence of constitutional judges by the proposing body, the House of Representatives.